Functional Evaluation Of Shoulder by Constant Score On Bandung Baseball Team - Leonardo Lubis (Jurnal Ergonomi dan K3, 2017)
Throwing is a repeatedly movement in Baseball. This activity will make Baseball athlete susceptible to suffer shoulder joint injury. Injuries to the shoulder joint will decrease the function of the shoulder joint. Therefore, it is necessary to do early detection to prevent further injury. Constant score is one method that used to assess the shoulder joint’s function. An analytic study performed on eighteen professional Bandung baseball athletes. Constant score form, which was consisted of subjective and objective questionnaires, filled out by the athletes. Scores were obtained from each question and grouped into five, as follow: Poor=